10.1001/TESTjama.2012.4607 (CrossRef Listing of Deleted DOIs, 2000)
IMPORTANCE: In May 2022, the US Food and Drug Administration (FDA) requested public comment on proposed rules to ban menthol in cigarettes and characterizing flavors in cigars. In 2024, the US Health and Human Services Secretary noted that a proposed ban on menthol cigarettes (MCs) would take more time given the high volume of public comments submitted. OBJECTIVE: To characterize the comments submitted to these dockets, including the sources and types of submissions and themes present in unique comments. DESIGN, SETTING, AND PARTICIPANTS: In this qualitative study, computer-assisted content analysis was conducted for public comments on the FDA's MC and flavored cigar (FC) proposed federal rules submitted from May to August 2022. Iterative data processing identified form letters and unique comments for thematic analysis in the MC comments and was applied to the FC comments. Informed by a validated codebook, deductive automated content analysis identified themes in unique comments. Analyses were conducted from October 2023 to December 2024. MAIN OUTCOMES AND MEASURES: The primary outcomes were identification of comments as form letters, duplicates, or unique, and whether they included arguments for and against the FDA's proposed rules. RESULTS: Of 246 808 comments submitted to these dockets (175 285 comments in the MC docket and 71 523 in the FC docket), most were identified as form letters (169 440 MC comments [97%]; 66 640 FC comments [93%]), with only 4774 comments (2%; 3342 MC comments and 1432 FC comments) identified as unique. Content tied to specific tobacco companies was identified in 44% of comments in the MC docket (77 445 comments) and 10% in the FC docket (6883 comments). Most unique comments opposed these bans (3208 MC comments [96%]; 1418 FC comments [99%]), with themes that addressed loss of revenue and sales (1155 MC comments [35%]; 720 FC comments [49%]), illicit market concern (835 MC comments [25%]; 555 FC comments [38%]), and suggesting more effective routes (607 MC comments [18%]; 420 FC comments [28%]) for action than the proposed policies. CONCLUSIONS AND RELEVANCE: In this study of nearly 250 000 public comments submitted to inform FDA rulemaking, most comments were form letters that reflected tobacco company talking points. These findings raise concerns about corporations co-opting mechanisms for public comment and distorting the prevalence of arguments to influence public health policy.